Administrative and Managerial Practices in Government and Private Tahfiz Schools in Selangor: a Comparative Analysis - Youcef Bensala (Al-Bayān, 2025)
This study explores the administrative and managerial practices of government and private Tahfiz schools in Selangor, Malaysia. Despite their shared objective of Quran memorization and religious education, these institutions differ significantly in governance structures, financial sustainability, and quality assurance mechanisms. Using a qualitative research design, data were collected through semi-structured interviews with ten school principals (five government, five private). The findings reveal that government Tahfiz schools operate under structured oversight by the Selangor Islamic Religious Department (JAIS), ensuring financial stability, standardized teacher training, and a balanced integration of academic and Tahfiz curricula. However, bureaucratic constraints limit flexibility in decision-making. Conversely, private Tahfiz schools enjoy greater autonomy in curriculum development and school operations but face significant financial challenges, inconsistent teacher qualifications, and a lack of standardized assessment procedures. The study identifies key areas where government and private Tahfiz schools can collaborate to improve educational outcomes, including enhancing teacher development programs, establishing quality assurance benchmarks, and implementing sustainable financial strategies such as waqf (endowments) and zakat allocations. The research underscores the need for policy reforms that bridge the gap between structured regulation and institutional flexibility, ensuring that both government and private Tahfiz schools contribute effectively to the holistic development of Quran memorizers. These findings provide insights for policymakers, educational administrators, and stakeholders seeking to elevate the standards and sustainability of Tahfiz education in Malaysia.